Increasing the nutritional value of strawberry puree by adding xylo-oligosaccharides. Issue 4 (April 2020) - Dai, Haochen; Leung, Caroline E.; Corradini, Maria G.; Xiao, Hang; Kinchla, Amanda J.
Abstract: The present study identified the threshold concentration of xylo-oligosaccharides (XOS) that resulted in minimal quality changes (rheology, color, water activity, pH, and total soluble solids) in strawberry puree. Optimization of XOS concentration to 5% (w/w) did not significantly alter the quality attributes of the strawberry puree. In addition, this study also monitored the rheological properties, composition (total soluble solids, total phenolic content, flavonoids, and tannin content), physicochemical attributes (color, water activity, pH) and sensorial properties of XOS-enhanced (5%, w/w) strawberry puree after thermal processing (HTST: 75 °C, 15s and UHT: 121 °C, 2s) and storage after 1, 15, and 36 days at 4 °C and 55 °C. At 5% (w/w) concentration, the addition of XOS increased consumer preference without significantly compromising quality attributes. Thermally treated strawberry puree (HTST and UHT) were less preferred by consumers than fresh puree. However, all strawberry samples incorporated with XOS (5%, w/w) received statistically higher scores than the samples without the XOS addition. Thus, the proposed supplementation of strawberry puree with XOS could be a viable solution to increase consumers' dietary fiber intake with little need for behavioral changes. Abstract : Food science; Food technology; Xylo-oligosaccharides; Strawberry puree; Thermal treatment; Sensory evaluation; Nutritional value; Shelf-life analysis.